Effectiveness of Chitosan-Based Edible Coating on Wax Jambu (Syzygium samarangense) - N. P. Minh (Journal of Global Pharma Technology, 2016)
Chitosan is a biodegradable material derived from chitin. It is used in agriculture industry. It has an antifungal property. Cinnamic acid is known as the agent of antimicrobial. Cinnamic acid is rarely used in single coating but tend to be used in combination coating. Coating is used to protect the food and conserve their shelf life. Wax jambu (Syzygium samarangense) fruits have a thin red skin and are delicate; they need to be picked by hand twice a week and handled with care. The fruits of S. samarangense are also having several medicinal properties they are highly perishable under post-harvest condition. This problem is an obstacle to the production of wax jambu for export. Objective of this study focused on the effectiveness of chitosan-based as edible coating on wax jambu (Syzygium samarangense) to extend its product’s shelf life. Results showed that wax jambu (Syzygium samarangense) was coated by 1.5% chitosan and 3.5 mM cinnamid acid which were appropriated to extend its shelf life for 10 days under ambient condition. Chitosan coatings can be used for storage of highly perishable fruits as it had showed increase in the shelf life of wax jambu. Chitosan ensures to slow down senescence by preventing respiration and transpiration.Keywords: Chitosan, Cinnamid acid, Coating, Shelf life, Syzygium samarangense.